2002
DOI: 10.1021/jp0142177
|View full text |Cite
|
Sign up to set email alerts
|

PES Studies of Ru(dcbpyH2)2(NCS)2 Adsorption on Nanostructured ZnO for Solar Cell Applications

Abstract: The interaction between the dye cis-bis(4,4′-dicarboxy-2,2′-bipyridine)-bis(isothiocyanato)-ruthenium(II), Ru(dcbpyH 2 ) 2 (NCS) 2 , and nanostructured ZnO was investigated by photoelectron spectroscopy (PES) using synchrotron radiation. The results are compared with those of nanostructured TiO 2 sensitized with the same dye, which to date is the most efficient system for dye-sensitized photoelectrochemical solar cells. When comparing the two metal oxides, differences in the surface molecular structure were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(101 citation statements)
references
References 27 publications
6
94
1
Order By: Relevance
“…[172] They found that such a complex layer could always be observed if the immersion time was longer than 3 h. Below an immersion time of 10 min, no complex was formed. Westermark et al [173] and Chou et al [174] verified that a short sensitization time may be favorable to avoid the formation of Zn 2þ /dye complex. However, the formation of the Zn considerable difference in the optimization of the sensitization time.…”
Section: Formation Of Zn 2þ /Dye Complexmentioning
confidence: 99%
“…[172] They found that such a complex layer could always be observed if the immersion time was longer than 3 h. Below an immersion time of 10 min, no complex was formed. Westermark et al [173] and Chou et al [174] verified that a short sensitization time may be favorable to avoid the formation of Zn 2þ /dye complex. However, the formation of the Zn considerable difference in the optimization of the sensitization time.…”
Section: Formation Of Zn 2þ /Dye Complexmentioning
confidence: 99%
“…For example, thin films of ZnO have been reported to display good conductivity and high transparency in the visible region, and have been envisaged as transparent electrodes for solar cells. [1] Zinc oxide nanoparticles have also been investigated as gas sensors [2] and materials for electrodes, [3] and, recently, an ultraviolet lasing effect has been observed at room temperature using ZnO nanowires. [4] These fascinating examples are based on the control of both the physical and chemical properties of the nanoparticles, which depend on several factors, namely the particle size and size dispersity, the shape of the particles, the surface state, the crystal structure, the organization of the particles onto a support, and their dispensability.…”
Section: Introductionmentioning
confidence: 99%
“…The most evident approach was to explore the two other main polymorphs of TiO 2 : brookite [22] and rutile, where the latter can enhance the scattering characteristics of the reflecting layer owing to its higher refractive index [23]. Alternatively, ZnO [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] [61,62]. So far, the anatase TiO 2 remains the leading contender photoanode as it affords the best performances of charge collection.…”
Section: Dye-sensitized Solar Cells Principle: Role and Progress In Tmentioning
confidence: 99%